Molecular dynamics simulations of solution mixtures and solution/vapor interfaces - Chen, Feng (Kansas State University, 2010)
In the past several decades, molecular dynamics (MD) simulations have played an important role in providing atomic details for phenomena of interest. The force field used in MD simulations is a critical factor determining the quality of the simulations. Kirkwood-Buff (KB) theory has been applied to study preferential interactions and to develop a new force field. KB theory provides a path from quantities determined from simulation data to the corresponding thermodynamic data. Here we combine KB theory and molecular simulations to study a variety of intermolecular interactions in solution. First, a force field for the computer simulation of aqueous solutions of alcohols is presented. The force field is designed to reproduce the experimentally observed density and KB integrals for a series of alcohols, allowing for an accurate description of alcohols’ activity. Other properties such as the translational diffusion constant and heat of mixing are also well reproduced. Second, the newly developed force field is then extended to more complicated systems, such as peptide or mini-proteins, to determine backbone dihedral potentials energetics. The models developed here provide a basis for an accurate force field for peptides and proteins. Third, we have then studied the surface tension of a variety water models. Results showed that different simulation conditions can affect the final values of surface tension. Finally, by using the Kirkwood-Buff theory of solution and surface probability distributions, we attempted to characterize the properties of the Gas/Liquid interface region. The same approach is then used to understand the relationship between changes in surface tension, the degree of surface adsorption or depletion, and the bulk solution properties.
Keywords: MOLECULAR DYNAMICS; SIMULATION; THEORETICAL; PROTEIN; INTERFACE; Kirkwood-Buff; Biology, Molecular (0307); Chemistry, Biochemistry (0487); Chemistry, Physical (0494)